Mucinous adenocarcinomas arising from a retro-rectal hamartoma: Unusual malignant transformation of a tailgut cyst - María Recuero Pradillo; Carlos Quimbayo-Arcila; Beatriz Moreno Torres; Angel Romo Navarro; Juan- Sebastian Malo Corral; Juan Ruiz Martín (Archives of Clinical Gastroenterology - Peertechz Publications, 2019)
Retrorectal cystic hamartomas, or tailgut cysts, are rare congenital lesions that are usually present as tumors with a considerable size in presacral area. Frequently, these lesions are asymptomatic so the diagnosis may be delayed.